KEBIJAKAN INDONESIA TERHADAP IMIGRAN ILEGAL ASAL BANGLADESH DAN RESPON PEMERINTAH BANGLADESH - Rausa Septia Rani; Ahmad Jamaan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The problem of immigrants who come to threaten national security, especially illegal immigrants, the case of illegal immigrants is a concern for Indonesia because of the impact of their arrival. The case of immigrants from Bangladesh is one of the many cases of mmigrants who arrive, as the government of Bangladesh, its citizens are the responsibility of the Government of Bangladesh. However, the Bangladesh government seems indifferent to its citizens who violate immigration regulations in Indonesia, the study aims to find out how Indonesia's policies towards illegal immigrants from Bangladesh and how the Bangladesh government responds to its citizens who violate immigration regulations in Indonesia. This it study uses a descriptive method with technical qualitative analysis that begins with collecting, compiling, and providing valid data. The data for this study were obtained by primary techniques in the form of interview and secondary data collection from books, journals, documents and online media. These this study gives the final result in the form of deportation as a form of Indonesia's policy towards illegal immigrants from Bangladesh with costs charged to the immigrant family. Keywords: Immigration, Rudenim, Government of